Novel admixture for improvement of foundations on tropical expansive soils - Abba, Hadi A.; Sani, Lawal; Abubakar, Mahmoud Hijab; Daud, Zawawi (International Journal of Integrated Engineering, 2017)
: Black cotton soils have excessive shrinkage and swelling properties with respect to changes in the moisture conditions. Thus, construction on these soils may result in foundation problems. conventionally some approaches have been used to mitigate the problem by stabilization with lime or cement and which are relatively expensive for sustainability, an alternative stabilization was experimented with terrazzo waste. The polishing process of the terrazzo tiles produces a significant amount of waste slurry that itâ€™s disposal could pose some environmental pollution threat. Laboratory experiments were conducted to determine the suitability of terrazzo waste as admixture in the stabilization of black cotton soil. Natural moisture content, atterberg limits, maximum dry density and optimum moisture content parameters were determined using 2, 4, 6, 8 and 10% proportion of terrazzo waste admixture. The results of the parameter analysis found the natural moisture content was 23.43%, liquid limit varied from 32.8 to 56.5%, Plasticity index varied from 4.71 to 13.52%, MDD varied from 1.61 to 1.67 (g/cm3) and OMC from 8.5 to 22.6%, the CBR value was indicates unsuitability for use as a base and sub-base material. The terrazzo waste admixture produced can be used for stabilization with the potential to minimize the cost of waste disposal as well as provide substitute to the use of conventional stabilizers for use inÂ  places such as parks or pathways.